Temporal Dynamics of Attention Bias in Anxiety: An Eye Tracking Study - (:unkn) unknown (My University, 2022)
Behavioral reaction time (RT) measures, like the dot-probe and spatial cueing tasks, have shown that individuals with anxiety tend to bias their attention toward threat as compared to neutral stimuli. However, the literature has revealed mixed findings due to the simplistic calculation of attention bias (AB; i.e., Mean RT Threat – Mean RT Neutral). Research has shown that attention bias fluctuation (i.e., patterns of both vigilance and avoidance), is indicative of attention dyscontrol, which is evident in those with psychopathology. As such, the purpose of this study was to evaluate whether AB fluctuation via behavioral RT measures and eye-tracking, stands as a more viable and consistent measure of AB in predicting overall symptom severity. Participants were recruited from three different studies: contamination phobia (n=52), social phobia (n=43), and spider phobia (n=72). Behavioral RT measures were evaluated using the trial-level bias score (TL-BS) to calculate AB fluctuation. In terms of eye-tracking, participants were shown four pictures in four quadrants, which included target threat, general threat, pleasant, and neutral photos. Basic individual eye-tracking indices consisted of dwell time, fixation count, and average fixation duration. However, to evaluate the time course of AB fluctuation, we created novel eye-tracking ratio indices, which included (1) dwell time/net dwell time (2) glance count/fixation count, and (3) average fixation duration/fixation time. The results showed that more than traditional AB indices in behavioral RT measures or basic individual eye-tracking indices, AB fluctuation measures (i.e., TL-BS, temporal eye-tracking ratio indices), significantly predicted overall symptom severity after controlling for general emotional symptoms (p Overall, the findings suggest that beyond traditional measures of AB to threat, temporal AB fluctuation indices should be given greater consideration when developing future theoretical, assessment, and intervention work related to anxiety disorders. Future research in AB modification may consider incorporating attention control components, which may be a promising treatment to reduce anxiety psychopathology.
Keywords: anxiety; attention bias; contamination phobia; eye tracking; social anxiety; spider phobia